Somatic mutations altering EZH2 (Tyr641) in follicular and diffuse large B-cell lymphomas of germinal-center origin - Morin, Ryan D; Johnson, Nathalie A; Severson, Tesa M; Mungall, Andrew J; An, Jianghong; Goya, Rodrigo; Paul, Jessica E; Boyle, Merrill; Woolcock, Bruce W; Kuchenbauer, Florian; Yap, Damian; Humphries, R Keith; et al. (Nature genetics, 2010)
Marco Marra and colleagues identify somatic mutations in EZH2 in diffuse large B-cell lymphomas and follicular lymphomas. EZH2 is a histone methyltransferase that participates in trimethylation of H3 Lys27 (H3K27) as part of the PRC2 complex. The mutations alter a single tyrosine residue in the SET domain of EZH2 and reduce the ability of PRC2 to trimethylate H3K27 in vitro . Follicular lymphoma (FL) and the GCB subtype of diffuse large B-cell lymphoma (DLBCL) derive from germinal center B cells 1 . Targeted resequencing studies have revealed mutations in various genes encoding proteins in the NF-κB pathway 2 , 3 that contribute to the activated B-cell (ABC) DLBCL subtype, but thus far few GCB-specific mutations have been identified 4 . Here we report recurrent somatic mutations affecting the polycomb-group oncogene 5 EZH2 , which encodes a histone methyltransferase responsible for trimethylating Lys27 of histone H3 (H3K27). After the recent discovery of mutations in KDM6A ( UTX ), which encodes the histone H3K27me3 demethylase UTX, in several cancer types 6 , EZH2 is the second histone methyltransferase gene found to be mutated in cancer. These mutations, which result in the replacement of a single tyrosine in the SET domain of the EZH2 protein (Tyr641), occur in 21.7% of GCB DLBCLs and 7.2% of FLs and are absent from ABC DLBCLs. Our data are consistent with the notion that EZH2 proteins with mutant Tyr641 have reduced enzymatic activity in vitro .